Comportamento parlamentar na Assembleia Legislativa de Minas Gerais: esquerda, direita ou algo mais? - Santos, Ana Cláudia Ribeiro (2023)
The theme of political ideologies has an extensive historical trajectory and plays a crucial role in contemporary society. Since at least the French Revolution, terms like "right" and "left" have been widely used to express fundamental differences in the stances of various political actors, including parties, representatives, and voters. Although there is a variety of ways in which these terms are employed, they continue to be present in the political debate. Therefore, the challenge is not so much to prove their legitimacy but rather to analyze the criteria for their legitimation. For this reason, Brazilian literature investigating the behavior of parties, governments, parliamentarians, and voters has been dedicated to examining the extent to which these actions are influenced by ideologies. Inspired by this context, the aim of this study is to understand whether the ideological position of political parties permeates their representatives' parliamentary actions today. To achieve this goal, we analyzed roll call votes on bills that occurred during the 18th and 19th legislatures of the Minas Gerais State Legislative Assembly. The adopted methodology included calculating association for each bill using the chi-square and Fisher's exact tests. The obtained results do not fully support the thesis of ideological coherence, as they indicate that even in issues with a clear ideological dimension, especially those extending beyond the traditional dimension related to the size of the State, ideology does not necessarily prevail. The majority of legislators position themselves differently than expected from a political-ideological standpoint, suggesting that an approach solely based on leftright perspectives is insufficient to comprehend arliamentary behavior in the subnational context of Minas Gerais. Other factors, such as the system of "state ultra-presidentialism" and geographic districts, exert significant influence on the decision-making process in voting.